The Implementation of Blue Economy Concept in Indonesia Marine and Fisheries Governance 2017-2022 - Fadhlillah, Nibras (Ikatan Da'i Indonesia, 2025)
The significant potential of marine and fisheries resources has given rise to a new economic development concept focusing on utilizing marine and fisheries resources through effective and sustainable marine governance – also known as the Blue Economy concept. The Blue Economy Concept was introduced by Gunter Pauli in 2009, which gained further prominence and was specifically discussed at the Rio+20 Meeting in 2012. Given with the abundant marine and fisheris resources, the concept has captured the attention of Indonesian government as a means to improve its national marine and fisheries sector while supporting its national economic development. This article is expected analyze and explain Indonesian government implementation of Blue Economy concept, particulalry on the governance of Indonesian marine and fisheries sector from 2017 – 2022. It is also expected to deliver a better understanding of policies and strategies undertaken by Indonesia government in comprehending the potential implication and the long-term sustainability of this new economic development concept. This article used a qualitative research method with desk/library research and qualitative interviewing as the data collection method. By critically examining Indonesia government response and implementation of the Blue Economy concept, the article aims to provide insight and recommendations of the potential areas for the improvement to ensure the responsible and sustainavle utilization of Indonesia marine and fisheries resources.